How Does Internal Migration Affect the Emotional Health of Elderly Parents Left-Behind? - Juliane Scheffel; Yiwei Zhang (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
The ageing population resulting from the one-child policy and the massive internal migration in China pose major challenges to elderly care in rural areas where elderly support is based on a traditional inter-generational family support mechanism. We use data from the first two waves of the China Health and Retirement Longitudinal Study to examine how migration of an adult child affects the emotional health of elderly parents left-behind. We identify the effects by applying fixed-effects and instrumental variable regressions which both identify the effect based on different sources of variation. We find that migration significantly reduces overall life-satisfaction by 8.8 percent and leads to an 8.7 (12 percent) percent higher probability of suffering from depressive symptoms (loneliness). Emotional health outcomes drastically deteriorate with reduced emotional support. In contrast to other developing countries, remittances cannot buffer the negative effects of emotional health. As emotional health is a key determinant of the overall health status, our findings have significant impacts for rural areas.
Keywords: I15; J14; O15; 330